Perception of Outpatients at Internal Medicine Polyclinic at RSUD Panembahan Senopati Bantul based on Nine Factors of Marketing Mix - Vianisa, Nurzahra; Dewanto, Iwan; Hidayah, Nur (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
RSUD Panembahan Senopati Bantul is a government-owned hospital that has experienced a decrease in the number of outpatients. High patient perceptions describe a good marketing mix of hospitals. The study aims to describe the patient's perception of the nine elements of the marketing mix in the Internal Polyclinic in the RSUD Panembahan Senopati Bantul. This type of research is descriptive with cross sectional methods. The total number of respondents is 110 patients that were found in the field, with convenience sampling techniques. The data type uses a questionnaire with the Likert option. Perceptions of outpatients in Internal Medicine Polyclinic at RSUD Panembahan Senopati Bantul against marketing mix majority well can be seen from average answer scores product (462.3), process(457.7), place (456), promotion (455.9) and considered poor on elements physical evidence (453.7), people (424.3), power (414.5), performance (412.5), and price (395.8). BPJS and General patient in Internal Medicine patients' perceptions of the nine majority marketing mix on product, process, place, and promotion elements is good.